ANALISIS PENGARUH ONLINE CUSTOMER REVIEW DAN RATING TERHADAP MINAT BELI PRODUK ELEKTRONIK DI E-COMMERCE TOKOPEDIA - Aditya Farhan Hasrul (2021)
This study uses a quantitative descriptive method which was carried out on Tokopedia users mainly in jakarta. Tokopedia is an e-commerce company (electronic commerce) type of marketplace from Indonesia which was officially launched to the public on August 17, 2009. The purpose of this research is to find out and analyze whether the customer review, customer rating, rating volume, information quality affect the purchase intention of electronics products in Tokopedia e-commerce marketplace. Samples taken were 100 respondents with the side probability method. Data collection was carried out by distributing questionnaires. The data analysis technique used is descriptive analysis and inferential analysis with the analytical tool used is PLS (Partial Least Square). The results showed that (1) Customer Review has an influence on purchase intention, with original sample value of 0.255 (2) Customer Rating has no effect or insignificant impact on purchase intention, with original sample value of 0.000 (3) Rating Volume has no effect on purchase intention with original sample value of 0.026 (4) Information Quality has significant impact on purchase intention, with original sample value of 0.462 The result of R-Square purchasing decision is 0.464, indicating a very strong research model and means that Customer Review, Customer Rating, Rating Volume and Information Quality together have a real contribution to the Purchase Intention of Electronic Products in Tokopedia is 46.4%.